Transmission of COVID-19 between Animals and Humans: A challenge for the Scientists - Ehsan Mostafavi; Zohre Eftekhari; Nazanin Jabbari; Parisa Gheibi (Pasteur Institute of Iran, 2021)
In recent decades, some 30 new human pathogens have been identified, of which 75% were spillovers from animals. In late 2019, human infections with a new coronavirus from an unknown origin emerged in China and later spread worldwide. The zoonotic source of severe acute respiratory syndrome coronavirus 2 remains unknown, and there is only some limited information about the close association between the first human cases of COVID-19 and visiting animal markets. Now, bats and pangolins are suspected as natural hosts, and large cats, raccoon dogs, dogs, minks, ferrets, and pangolins as intermediate hosts.  There is not enough evidence to prove that animals can transmit COVID-19 infection to humans, but there are some data about the transmission of SARS-CoV-2 between humans and some animal species.